Pengukuran Kualitas Pelayanan (Servqual-Parasuraman) dalam Membentuk Kepuasan Pelanggan Sehingga Tercipta Loyalitas Pelanggan: Studi Kasus pada Toko Mayang Collection Cabang Kepanjen - Sinollah Sinollah; Masruroh Masruroh (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
This study aims to analyze customer satisfaction at Mayang Collection, test and explain the effect of servqual dimension service quality (physical evidence, reliability, responsiveness, confidence, and empathy) on customer satisfaction at Mayang Collection, and test and explain the effect of customer satisfaction on customer loyalty on Mayang Collection. The population in this study were customers of the Mayang Collection Kepanjen store who had a member card and made a repeat purchase. Population research or population study so that the number of samples in this study is a number of population, amounting to 93 respondents. The method used in this research is explanatory survey method, which is a method used to explain causal relationships between variables through hypothesis testing (Nazir, 2005). Based on the results of the static test all the indicators in this study are valid, and the variables are reliable. The results of the servqual analysis show that the difference or gap between customer expectations and employee performance has a total average which is at the moderate classification level (Parasuraman table, 1990) or service quality in Mayang Collection stores is quite good. This means that customer satisfaction in terms of quality of service provided at Mayang Collection is quite good. The path analysis test results (path analysis) show that there is no significant influence between servqual dimension service quality (physical evidence, reliability, responsiveness, confidence, and empathy) to customer satisfaction. This proves that service quality has a long-lasting influence in shaping customer satisfaction. And customer satisfaction has a significant influence on customer loyalty. Mayang Collection stores are advised to pay more attention to and improve other factors besides service quality in increasing customer satisfaction, because with increasing customer satisfaction, customer loyalty will be formed easily.